Women-led development through micro-finance led interventions: Myths or reality? - Divya Singh Chandel; Nitin Gupta (Social Sciences and Humanities Open)
Women play a crucial role in addressing global challenges, yet systemic barriers hinder their progress. This study examines microfinance-led interventions in India, chosen for its extensive SHG-bank linkage program, to assess their impact on women's empowerment. A bibliometric analysis using PRISMA, VOSviewer, and Biblioshiny highlights that while microfinance enhances financial inclusion and entrepreneurship, socioeconomic and cultural barriers limit its effectiveness. Findings suggest integrating non-financial services, such as leadership training, to maximize impact. These insights aid policymakers in designing holistic microfinance strategies, fostering gender equality, societal well-being, and sustainable development in alignment with SDGs.